Cocoa pod husk: a new source of CLEA-lipase for preparation of low-cost biodiesel: an optimized process - Khanahmadi, Soofia; Yusof, Faridah; Ong, Hwai Chyuan; Amid, Azura; Shah, Harmen (Elsevier, 2016)
Cocoa pod husk (CPH) is a by-product of cocoa production obtained after removing the beans from the fruit. The analysis of CPH has shown that it contains high amounts of protein. This study is aimed to utilize this protein source in hydrolase enzyme production. In this study, seven hydrolase enzymes (amylase, fructosyltransferase, mannanase,glucosidase, glucanase, lipase and protease) were screened from CPH for the first time for feasible industrial production. Among these hydrolases, lipase was chosen for the next steps of experiments as it has a lot of applications in different industries.The extraction of high active lipase from CPH has been done under optimum conditions.The condition that was optimum for the three major factors was achieved using Face centered central composite design (FCCCD) with response surface methodology (RSM) to obtain the highest enzyme activity of crude lipase from CPH. The optimum condition of extraction is used for preparation of cross-linked enzyme aggregate (CLEA). For the production of immobilized biocatalyst, the technique of CLEA is considered as an effective technique for its industrially attractive advantages. Referring to the results of OFAT, CLEA-lipase was prepared in the best condition at the presence of 30 mM ammonium sulphate, 70 mM glutaraldehyde with 0.23 mM Bovine serum albumin as an additive. Immobilization effectively improved the stability of lipase against various organic solvents